Pengaruh Variasi Produk Dan Trend Fashion Terhadap Minat Beli Konsumen Pada Toko Happy Tuhfah Kecamatan Gandapura - Nadhila Fitria; Zahraini Zahraini; Yusrawati Yusrawati; Al Mahfud Saputra (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The rapid growth of the fashion industry has encouraged retail businesses to better understand the factors influencing consumer purchase intention. Product variety and the ability to follow fashion trends have become important strategies in increasing product attractiveness amid increasingly competitive market conditions. This study aims to analyze the effect of product variety and fashion trends on consumer purchase intention at Happy Tuhfah Store in Gandapura District. This study employed a quantitative approach with an associative research design. The sample consisted of 67 respondents selected using simple random sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that product variety and fashion trends have a positive and significant effect on consumer purchase intention, both partially and simultaneously. Product variety was found to be the most dominant variable with a regression coefficient of 0.885, while fashion trends had a coefficient of 0.509. Furthermore, the coefficient of determination of 0.892 indicates that 89.2% of the variation in consumer purchase intention can be explained by these two variables, while the remaining portion is influenced by other factors outside this study. The findings suggest that product diversity and the ability to adapt to current fashion trends are important factors in increasing consumer purchase intention in local fashion retail businesses.